Access to Microfinance Effect and Economic Welfare - wiwin setyari (Trunojoyo University of Madura, 2019)
The leaders of Southeast Asia countries have called for the formulation of a strategic plan to accelerate and realize the vision of doubling the financial inclusion in the ASEAN region in 2020. Regional approach for financial inclusion has been identified as one important factor for national development in many ASEAN countries. In addition, it has also become an important strategy to support the broader goals of regional economic integration as contained in the blueprint of the ASEAN Economic Community (AEC). The deepening of the financial sector is one of the main objectives in the AEC. It mainly affects the capital and capacity constraints on the financial system in several ASEAN countries, including Indonesia.Lembaga Perkreditan Desa or LPD is a traditional micro finance institution in Bali. It is called traditional because they operate based on local government regulation which roots from traditional village rules (namely awig-awig). Both of LPD strength and weakness lies on their limited operational areas within a traditional village as tightly regulated in awig-awig. Microfinance institutions, including the LPD, became the foundation to achieve the main goals of financial inclusion in Indonesia.This study tries to look beyond the influence of access to the LPD, through public perception point of views about distance, interest rate, and service to improve Balinese people welfare. Tests carried out using cross section OLS to retrieve data from interviews of 107 respondents who become LPD customers. The results of this study are expected to provide further description whether access to the LPD affect the increase in the welfare of society, especially access to microfinance institutions.